Macroeconomic and Economic Policy Uncertainty on Index Movement: An Empirical Study of the Islamic Capital Market in Indonesia - Wafi, Faiq Maulana; Merlinda, Santi (UIN Siber Syekh Nurjati Cirebon, 2023)
As seen by capitalization value increase and investor interest, Indonesian Islamic capital markets are developing. This research examines the long-term effects of macroeconomic factors and U.S. economic policy uncertainty on the Jakarta Islamic Index (JII) and its reaction to macroeconomic shocks and the US EPU from January 2018 to September 2022. Inflation, exchange rates, GDP, and EPU, are macroeconomic factors analyzed with Vector Error Correction Model (VECM). This research shows long-term GDP affects the Jakarta Islamic Index (JII). In structural analysis, JII capitalization responds volatilely to Inflation, positively to exchange rate movement (USD/IDR), and adversely to US GDP and EPU. This analysis also shows that the exchange rate (USD/IDR rate) explains the JII variable the most, followed by the US EPU, GDP, and Inflation.Keywords: JII; Inflation; Exchange rate; GDP; US EPU